Esthetic solution to malpositioned implants with remodeling of soft tissue: A case report - Valente, Mariana Lima Da Costa; Marcantonio, Elcio [UNESP]; Faeda, Rafael Silveira; De Paula, Wagner Nunes; Dos Reis, Andréa Cândido (My University, 2016)
This article describes a clinical case of gingival conditioning with provisional fixed prostheses to improve the esthetics of the soft tissues adjacent to fixed prostheses placed on malpositioned implants. Gradual application of pressure to the tissues is an easy, nontraumatic technique for inducing formation of papillae and reestablishing the appropriate shape and contour of the gingival tissues, thereby improving esthetics and phonetics. The proposed treatment proved to be effective in remodeling the surrounding soft tissues, providing suitable contours, and restoring esthetics and function lost due to surgical treatment with malpositioned implants.
Keywords: Connective tissue; Dental implants; Gingiva